Constitutive CD40 signaling calibrates differentiation outcomes in responding B cells via multiple molecular pathways - Basu, Srijani; Kaw, Sheetal (The journal of immunology, 2016)
CD40 signaling during B cell activation is known to inhibit terminal differentiation and promote memory generation. Blimp-1 is essential for efficient plasma cell (PC) generation, and although CD40 signaling is known to inhibit Blimp-1 induction during B cell activation, the mechanisms involved have been unclear. We report that CD40 signaling induces miR-125b that targets Blimp-1 transcripts, and increases amounts of the ubiquitin ligase Hrd1 that targets BLIMP-1 protein for proteasomal degradation. CD40 signaling also inhibits the early unfolded protein response (UPR) of activated B cells that precedes the induction of terminal differentiation, and Hrd1 feeds into this pathway by targeting the core UPR component IRE-1α. Strikingly, CD40 signaling in the absence of BCR- or TLR-ligation also repressed Blimp-1 transcripts, suggesting that noncognate ligation of CD40 via T-B interactions may repress Blimp-1 in vivo. In support of this, we find that naive B cells purified from CD40-CD154 interaction-deficient mice express higher amounts of Blimp-1 and lower amounts of microRNAs and Hrd1. Higher basal amounts of Blimp-1 in naive CD40−/− B cells correlate with an increased tendency of the cells to undergo terminal differentiation upon LPS stimulation. Conversely, a 24-h exposure to CD40 ligation during LPS stimulation of wild-type B cells is sufficient to inhibit PC generation. The data show that CD40-mediated inhibition of PC generation is via engagement of multiple pathways that involve repression of Blimp-1 and inhibition of the UPR that prepares cells to become professional secretors. They also show that constitutive CD40 signaling in vivo involving bystander T-B interactions can calibrate B cell differentiation outcomes.
Gesehen am 04.12.2018